2020
DOI: 10.1186/s12886-020-01724-2
|View full text |Cite
|
Sign up to set email alerts
|

Consistency between optical coherence tomography and humphrey visual field for evaluating glaucomatous defects in high myopic eyes

Abstract: Background The study is to investigate the influence of high myopia on the consistency between optical coherence tomography (OCT) and visual field in primary open-angle glaucoma (POAG). Methods We enrolled 37 patients with POAG with high myopia (POAG-HM group), 27 patients with POAG without high myopia (POAG group), and 29 controls with high myopia (HM group). All subjects underwent Humphrey perimetry (30–2 and 10–2 algorithms). The peripapillary retinal nerve fiber layer (RNFL) and macular ganglion cell-inne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The poorer OCT scan quality obtained in myopic eyes and the greater circumference due to larger OCT scan may contribute to this condition 53. Third, various morphologic changes are commonly found in the optic disc in high myopia, including tilted or torsional disc, abnormal optic disc size, peripapillary atrophy, which will also interfere with the accuracy of RNFL thickness measured by OCT and the evaluation of glaucoma severity 54,55. Forth, most of the OCT instruments did not include high myopia in the internal normative database nowadays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poorer OCT scan quality obtained in myopic eyes and the greater circumference due to larger OCT scan may contribute to this condition 53. Third, various morphologic changes are commonly found in the optic disc in high myopia, including tilted or torsional disc, abnormal optic disc size, peripapillary atrophy, which will also interfere with the accuracy of RNFL thickness measured by OCT and the evaluation of glaucoma severity 54,55. Forth, most of the OCT instruments did not include high myopia in the internal normative database nowadays.…”
Section: Discussionmentioning
confidence: 99%
“…53 Third, various morphologic changes are commonly found in the optic disc in high myopia, including tilted or torsional disc, abnormal optic disc size, peripapillary atrophy, which will also interfere with the accuracy of RNFL thickness measured by OCT and the evaluation of glaucoma severity. 54,55 Forth, most of the OCT instruments did not include high myopia in the internal normative database nowadays. Therefore, when comparing the thickness in high myopia to that of a built-in normative database, non-glaucomatous myopia present false-positive results in OCT color probability codes, which is known as "red-disease".…”
Section: Diagnostic Difficulties Of High Myopia Glaucoma With the Use...mentioning
confidence: 99%
“…The characteristic glaucomatous visual field defects were Bjerrum, Seidel, paracentral scotoma, or nasal step on Humphrey visual fields, with clusters of three or more adjacent points depressed by >5 dB or two adjacent points depressed by >10 dB. [ 7 , 8 ]…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have demonstrated that the ganglion cell complex (GCC) parameters are superior to RNFL at detecting glaucoma in the context of high myopia [ 77 , 78 , 79 , 80 , 81 ]. Vertical scans of the macula have also been shown to be useful for evaluating RNFL thickness in myopic eyes [ 82 ].…”
Section: Diagnostic Challengesmentioning
confidence: 99%
“…Vertical scans of the macula have also been shown to be useful for evaluating RNFL thickness in myopic eyes [ 82 ]. Whilst RNFL has been found to correlate with refractive error, GCC was found to have no significant relationship with refractive error, and furthermore may better agree with visual field defects as compared to RNFL [ 80 , 81 ]. While the results of a meta-analysis found no significant differences between the two parameters, a more recent longitudinal study found that highly myopic eyes with progressive macula ganglion–inner plexiform layer thinning had a significantly higher risk of developing visual field defects, while there was no correlation with RNFL thinning, in contrast to non-myopes [ 83 , 84 ].…”
Section: Diagnostic Challengesmentioning
confidence: 99%